Digital Game to Support the Effectiveness of Using Interactive e-Module on Vibration and Waves Concept (IeMVWC) - Saprudin Saprudin; Melwenti Sikti Januarsih; Nurdin Abdul Rahman; Rahmat Rizal (TECHNO: JURNAL PENELITIAN, 2023)
Digital games have the potential to increase the effectiveness of using interactive e-modules. This development research aims to produce an interactive e-module on vibration and waves concept (IeMVWC) assisted by digital games, as well as investigate the impact of its use on student learning achievement. This development research follows the ADDIE stages (Analyze, Design, Develop, Implement, and Evaluate). The data collected in this study includes product validation data, learning achievement data, and student response data collected through validation sheets, multiple-choice questions, and questionnaires. The IeMVWC product assisted by digital games produced is declared very feasible for use in learning and effective in improving student learning achievement in vibration and wave learning.